The Discovery of Deli Sultanate Currency in Batubara, North Sumatra - Saparudin Barus; Singgih Tri Sulistiyono; Yety Rochwulaningsih (Journal of Maritime Studies and National Integration, 2021)
This paper aims to explain the finding of the Deli Sultanate Currency that shows the Deli Sultanate existence and heyday of trade in 19th century. By the used of historical method, this paper emphasized the finding of the Deli Sultanate coins in Batubara which was a form of power contestation in the trading system. Deli Sultanate coins found in the Batubara trading port area cannot be separated from the involvement of international trade activities. The contestation in the trading space in the 19th century was dominated by the British and the Dutch. Meanwhile, the finding of Deli Sultanate coins proves that the contestation space was also enriched by a local kingdom.